2019
DOI: 10.1186/s12969-019-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of second-line therapy in IVIg-refractory Kawasaki disease: a systematic review

Abstract: BackgroundEvidence remains contradictory regarding second-line therapy in patients with Kawasaki disease (KD) refractory to initial intravenous immunoglobulin (IVIg). The objective of this study aims to evaluate the efficacy and safety of three treatments [i.e. a second IVIg infusion, methylprednisolone (IVMP), and infliximab (IFX)] in patients with refractory KD.MethodsA systematic search of PubMed, Embase, Cochrane, and ClinicalTrials.gov using predefined MeSH terms was performed from 1990 through 2017. Rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…If KD patients who receive 1 g/kg IVIG as initial treatment develop IVIG resistance, more aggressive additional treatment could therefore be given such as infliximab. Infliximab, a monoclonal antibody against tumor necrosis factor α, is more effective in fever resolution compared to a second IVIG dose 20,21 . Further studies are needed to determine the efficacy of infliximab in KD patients who do not respond to the initial 1 g/kg IVIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If KD patients who receive 1 g/kg IVIG as initial treatment develop IVIG resistance, more aggressive additional treatment could therefore be given such as infliximab. Infliximab, a monoclonal antibody against tumor necrosis factor α, is more effective in fever resolution compared to a second IVIG dose 20,21 . Further studies are needed to determine the efficacy of infliximab in KD patients who do not respond to the initial 1 g/kg IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab, a monoclonal antibody against tumor necrosis factor α, is more effective in fever resolution compared to a second IVIG dose. 20 , 21 Further studies are needed to determine the efficacy of infliximab in KD patients who do not respond to the initial 1 g/kg IVIG. If this problem is properly handled, 1 g/kg IVIG could be a cost‐effective treatment option for KD patients.…”
Section: Discussionmentioning
confidence: 99%
“…KD is a common cause of vasculitis in childhood, which is characterized by fever and mucocutaneous features [13]. Current studies suggest that the regulation of T cell activation determines the susceptibility of KD and the severity of coronary artery lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 27 It is concluded that infliximab monotherapy should be considered in patients, who fail to respond to initial IVIG, based on a systematic review of the literature with pooled outcome data analysis suggesting infliximab is more effective in fever resolution compared to a second IVIG dose and intravenous methylprednisolone. 27 According to a 2019-Cochrane review, tumor necrotic factor (TNF) alpha blockers (TNF-α) may reduce treatment resistance and the infusion reaction of IVIG after treatment initiation; further research is, however, needed. 28 Subcutaneous etanercept with IVIG for acute KD was studied in a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%